Waste minimization in mid-scale hotels & restaurants in Metro Manila case study (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2006)
The efficient use of utilities has been a traditional way of controlling costs in hotels and restaurants and not deliberately as part of an environment protection initiative. This case study investigated waste minimization practices of four mid-scale establishments listed with the Hotel & Restaurant Association of the Philippines using a waste reduction assessment (WRA) method. Based on the concept of reducing waste generation at source to lessen or effect zero waste disposal, WRA was utilized to evaluate operations and determine appropriate cost-efficient and environmentally sound waste management alternatives. The areas and/or issues covered were energy, water, solid waste, effluents and emissions and environmental ethics. Analysis reveals high and uncontrolled water and energy use. The options illustrate savings with simple monitoring and conservation procedures. Materials resource management although primarily cost oriented needs to integrate waste segregation and recycling practices into operational procedures. The options show computed potential income from more aggressive recycling of solid waste. The effluents problem is crucial and requires pooling of resources among establishments for common treatment plants that eliminate contamination of water resources. Hotels and restaurants need programs to establish environmental policies and procedures as a corporate ethic.